Ear Foreign Body in Paediatric Patients: Methods of Removal and When to Refer. - Chuen, Chew Shiun; Othman, Nik Adilah Nik (Bangladesh Journal of Medical Science, 2019)
Paediatric patient with a foreign body in the ear may be present primarily to primary care physician or being referred to the otorhinolaryngology (ORL) clinic. The foreign bodies vary from organic to inorganic material with different sizes and shapes. Removal of foreign body in the ear canal requires adequate clinical experience as well as proper clinical instruments and cooperative clinical staff. Throughout the years, many clinical instruments and devices have been designed and proven to able to facilitate a smooth procedure with high success rates. However, an agitated child may be uncooperative and the increase in the number of attempts will result in injury of the ear canal or displacement of foreign body to the middle ear. Thus, clinical experience is essential and the doubtful cases are preferably to be performed under general anaesthesia to prevent complications. Bangladesh Journal of Medical Science Vol.18(2) 2019 p.423-426